DETERMINATION OF THE MINIMUM RESERVE INFUSION SOLUTIONFOR INTENSIVE CARE IN EMERGENCY AID TO VICTIMS EMERGENCY - I. V. Kochin; S. V. Gorpenko; D. A. Troshin; V. L. Kurochka (Медицинский вестник Юга России, 2015)
Purpose: to develop a science-based methodology for determining the need for infusion solutions needed to provide emergency medical care and follow-up treatment of the aff ected population in the liquidation of the health consequences of emergencies.Materials and methods: the analysis of legislative and regulatory framework in а sphere of public drug coverage for emergency medical assistance in emergencies. Th e methodological basis of research were the principles of the system, an integrated, process, logical framework approach to study the organization of activities of pharmacy chains in emergencies.Results: putting into practice the proposed evidence-based management allows health authorities and State Disaster Medicine Service plan and calculate an amount need of infusion solutions for emergency medical care in the aft ermath of the loss of health in emergencies. Application of the proposed method to optimize rational use of budgetary funds for the establishment of local, district and regional reserves infusion solutions for the liquidation of consequences of emergency situations.Summary: the proposed planning approach of minimum reserves of intravenous fl uids to provide intensive therapy requires further improvement of theoretical and methodological basis.